Evaluación de las coloraciones Papanicolaou y tricrómica en la tinción de protozoos ciliados ruminales (2011)
ABSTRACT: Ruminal ciliated protozoa show morphological differences between their orders, including the majority share of its internal structures varying in size, shape and spatial arrangement, which allows differentiation. Therefore, the colors we studied could be a useful tool for morphological identification of these organisms. Objective Evaluate Staining affinity and quality of the Pap staining and Trichrome staining in ruminal ciliated protozoa. Materials and methods Experimental study made from factorial designs analyzed through nonparametric tests. The Pap and Trichrome stains were tested with 36 treatments in triplicate. Results For PAP staining in the order Vestibuliferida the preservative formaldehyde 10% (p = 0.040) and time of alcohol exposure to 120 min (p = 0.046) showed statistically significant differences for the affinity; Entodiniomorphida order not present statistically significant in none of the factors, like quality to that color for the two orders. As Trichrome staining, we found that none of the orders had a significant effect of the factors evaluated on the response variable affinity, on the contrary, the quality showed significant differences for the two orders, the order Vestibuliferida showed significant differences using the preservative formalin 10% (p = 0.000) and fixed with Schaudinn 30 min (p = 0.023) and Entodiniomorphida only showed differences with the preservative formalin 10% (p = 0.002). Conclusions The coloring of the best results in both orders to the two response variables is the Papanicolaou stain.